Comparative study of testing the efficacy of injection meglumine antimoniate with oral itraconazole as first line treatment of cutaneous leishmaniasis: Treatment options for cutaneous leishmaniasis - Sultan, Nadia; Iftikhar, Ayusha; Barkat, Madiha; Rahman, Saima; Butt, Ghazala; Noor, Salman Jameel (Journal of Pakistan Association of Dermatologists, 2023)
Background Cutaneous Leishmaniasis is caused by different species of a protozoa.1 The disease is endemic in some areas of Pakistan like Baluchistan, Sindh, Khyber Pakhtunkhwa.2 There are many treatment options including meglumine antimoniate, rifampicin, tetracyclines, sodium sitbogluconate and itraconazole etc.3 Â Objective The objective of our study was to compare the efficacy of injection meglumine antimoniate with cap Itraconazole as 1st line treatment of cutaneous leishmaniasis. Â Methods This study on cutaneous leishmaniasis was conducted in the Dermatology Department at Punjab Ranger Teaching Hospital Lahore. All 20 male patients referred to us from the endemic area (Kashmore) were divided into two groups A and B after positive Slit Skin Smear test. Group A were given meglumine antimoniate 400mg/day intramuscular injection, group B were given Cap Itraconazole 200 mg per day for 4 weeks. Patients assessment was done on three criteria; 1: clinical resolution of lesions 2: side effects seen during the treatment 3: report of slit skin smear at 4 weeks. Â Results According to study results Slit Skin Smear test was 100% positive for all 20 patients before treatment, but came negative for all 10 patients of group A and negative for only 2 patients of group B after 4 weeks. Some side effects were observed during treatment in both groups but they were more in group A patients. Clinical resolution of lesions was 100% in Group A as compared to group B 20%. Â Conclusion Injection meglumine antimoniate is the preferred treatment of cutaneous leishmaniasis regards to its efficacy as compared to oral Itraconazole based on the clinical resolution & negative slit smear at the end of the course but the limitations to treatment are the poor patient tolerance & the increased side effects seen in this group. Â